Analysis o leadership style and motivation on turnover intention mediated by employee loyalty at PT. WOM finance - Wahyu Sungging; Adrie Fans Assa (Institute of Computer Science (IOCS), 2026)
Increasing competition in the financial services industry requires organizations to effectively manage and retain their human resources. Employees are strategic assets that play an essential role in achieving organizational goals, therefore the ability to maintain employee stability and loyalty is a key determinant of long term organizational success. One important indicator of human resource conditions is turnover intention, which reflects employees’ tendency to leave the organization. High levels of turnover intention may negatively affect organizational operations, increase recruitment and training costs, and reduce overall productivity. Consequently, organizations must understand the factors influencing turnover intention in order to formulate appropriate human resource management strategies. Within this context, PT WOM Finance, as a financing company operating in Indonesia, faces challenges in managing and reducing employee turnover intention. Organizational behavior literature indicates that leadership style and work motivation are critical factors influencing employee attitudes, loyalty, and behavioral intentions. Leadership style implemented by managers can influence employee motivation and shape employee loyalty toward the organization. Work motivation functions as an internal drive that determines the intensity, direction, and persistence of employee efforts in achieving organizational objectives. Employee loyalty represents emotional attachment and organizational commitment and is considered a mediating variable in the relationship between leadership style, motivation, and turnover intention. This study aims to analyze the effect of leadership style and motivation on turnover intention with employee loyalty as a mediating variable. A quantitative approach using a survey method was employed. Data were collected through structured questionnaires and analyzed using path analysis. The results indicate that leadership style and motivation have a positive effect on employee loyalty and also positively influence turnover intention, both directly and indirectly through employee loyalty within the financing organization